Recent trends in use of inferior vena caval filters in US older adults with acute pulmonary embolism. Issue 186 (February 2020) - Bikdeli, Behnood; Wang, Yun; Jimenez, David; Ross, Joseph S.; Gupta, Aakriti; Desai, Mayur M.; Parikh, Sahil A.; Monreal, Manuel; Goldhaber, Samuel Z.; Krumholz, Harlan M.
Highlights: Previous studies showed frequent use of IVC filters in older adults with pulmonary embolism (PE). Given the concerns for safety/efficacy, and reimbursement changes, we assessed the recent trends. There has been a decline in utilization of IVC filters among older adults with PE. The causes of the observed trends require further investigation.